Seed priming with ZNPs reduced expression of salinity tolerance genes in Glycine max L. and improved yield traits - Reda Mohamed GAAFAR; Mohamed Lotfi HALAWA; Adel Ramadan EL-SHANSHORY; Abdelhamid Abdelrahim EL-SHAER; Rana Hosny DIAB; Marwa Mahmoud HAMOUDA (Acta Agriculturae Slovenica)
Little has been done to evaluate the molecular role of ZnO nanoparticles (ZNPs) in regulating biochemical processes and plant yield in response to salt-induced stress. In this study, the molecular response of salt-stressed soybean (‘Giza111’) was assessed under different concentrations of ZNPs (25, 50, 100, and 200 mg l-1) by measuring some osmolytes, yield parameters, and Na+ and K+ content. The impact of salinity on the mRNA expression levels of three key salt-tolerance related genes (GmCHX1, GmPAP3, and GmSALT3) using qRT-PCR was also determined. The high level of salinity (250 mM NaCl) led to a significant increase in Na+ content, total soluble proteins, and total soluble carbohydrates and significantly upregulated gene expression of GmCHX1, GmPAP3, and GmSALT3, while reducing K+ content, K+/Na+ ratio and all yield parameters compared to control plants. Soaking soybean seeds in various ZNP concentrations, on the other hand, increased K+ content and K+/Na+ ratio while decreasing Na+ content, total soluble proteins, and total soluble carbohydrates in stressed plants, particularly at 50 mg l-1 ZNPs. Furthermore, GmCHX1, GmPAP3, and GmSALT3 expressions were all downregulated at 50 mg l-1 ZNPs, which ultimately improved soybean yield parameters. Accordingly, these results recommend the application of 50 mg l-1 ZNPs for improving the productivity of soybean cultivated in saline soils.